(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
We want to identify the perception about of the quality in service in the Instituto Mexicano del Seguro Social (IMSS), for the citizen in Aguascalientes city. The analysis has done in two dimensions: Attention and value in the service. The random survey has done to 348 people is organized so that there are two sets of questions with 5 variables for each analysis: The first section analyzes the attitude of the people who work for the realization of the service and second set qualifying the tangible features of it. The result indicates that the average perception of the population of the service, shows a great potential for improvement and two dimensions